Differentiated subsidy mechanisms for international railway transport and competitive strategies against maritime shipping - Lijing Du; Yufei Zhu; Song Lei; Heting Su; Qi Cai (Management System Engineering)
Abstract As a key mode of cargo transportation, railway freight faces challenges such as cargo source competition, excessive subsidies, and homogeneous competition. This study explores differentiated subsidy strategies for international railway freight transport and finds that while fixed subsidies can promote short-term development, interprovincial subsidy interactions significantly impact overall effectiveness. The study develops a three-level planning model to analyze the effects of cargo type and geographical differences on local government subsidy strategies. Using China–Europe Railway Express data as an example, the results indicate that subsidies are more effective for goods with low time sensitivity, and the optimal subsidy value varies depending on train routes and city locations. It is recommended that local governments implement differentiated subsidies, prioritizing low time-sensitive goods to promote the high-quality development of international railway transport.